A Study of Properties of Plasma Using Local Materials. - Kemigisha, Shallote (Kabale University, 2024)
This study utilized local materials, such as candles and common high school laboratory equipment, to design experiments demonstrating the unique properties of plasma as a state of matter, distinct from other states. The aim was to address the lack of practical lesson activities for the new senior topic in Uganda's revised lower secondary curriculum. The study used scientific literature to approximate plasma with locally available forms, designing and performing safe experiments to illustrate properties such as quasi-neutrality, the coexistence of independent opposite charges, response to electric fields, and temperature-dependent spectroscopy of plasma. The experiments successfully demonstrated these properties using candle flames and Bunsen burner flames.